The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1155/2015/189863
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Bypass and Oxidative Stress

Abstract: The development of the cardiopulmonary bypass (CPB) revolutionized cardiac surgery and contributed immensely to improved patients outcomes. CPB is associated with the activation of different coagulation, proinflammatory, survival cascades and altered redox state. Haemolysis, ischaemia, and perfusion injury and neutrophils activation during CPB play a pivotal role in oxidative stress and the associated activation of proinflammatory and proapoptotic signalling pathways which can affect the function and recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 99 publications
4
116
2
5
Order By: Relevance
“…It is considered that various factors such as surgical damage, CPB, and ischemia-reperfusion damage cause oxidative stress in ONCABG patients [20]. Haemolysis occurring in CPB, ischemia-reperfusion damage, and activation of neutrophils are important factors in the formation of oxidative stress [2]. Pumping period in heart surgery and aortic cross clamp period are important factors in ischemia-reperfusion damage [21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is considered that various factors such as surgical damage, CPB, and ischemia-reperfusion damage cause oxidative stress in ONCABG patients [20]. Haemolysis occurring in CPB, ischemia-reperfusion damage, and activation of neutrophils are important factors in the formation of oxidative stress [2]. Pumping period in heart surgery and aortic cross clamp period are important factors in ischemia-reperfusion damage [21].…”
Section: Resultsmentioning
confidence: 99%
“…Superoxide anion (O 2 −∙ ), hydrogen peroxide (H 2 O 2 ), hydroxyl radical ( ∙ OH), and peroxynitrite (ONOO − ) are the essential ROS types that cause oxidative damage in the heart [2]. Open heart surgeries performed with cardiopulmonary bypass induce oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that MAPK signaling is activated during CPB-triggered acute lung injury, and mediates cellular inflammation and permeability (20). Thus, the present study tested the phosphorylation of p38 MAPK and ERK to investigate the regulation of MAPK signaling by NAMPT under A-R treatment.…”
Section: Nampt Knockdown Restrains A-r-activated Mapk Signalingmentioning
confidence: 97%
“…It exposes RBCs to non-physiological stimuli modifying their integrity and role. CPB can damage RBC due to shear stress forces which make RBC less deformable and more fragile (J. F. Hoffman, 1962;Morariu, et al, 2004), thereby resulting in more free Hb in circulation (Baskurt & Meiselman, 2003;Morariu, et al, 2004;Saraf, Wellsted, Sharma, & Gorog, 2009;Zakkar, Guida, Suleiman, & Angelini, 2015). Furthermore; peri-operative blood transfusion can result in increased oxidative stress when stored blood is used due to diminish antioxidant properties or storage defect which is evident from ATP and 2,3-diphosphoglycerate depletion and increased lipid peroxidation (Karkouti, 2012;Relevy, Koshkaryev, Manny, Yedgar, & Barshtein, 2008;Zakkar, et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%